Growth of Turi Seedlings (Sesbania grandiflora L. Pers) on Ex-Gold Mining Land Using Organic Cow Stall Fertilizer in Polybags - Rahmawati; Gilang Ramadhan Syahputra; Annadira; Yusran; Siti Casandra Putri; Moh Rian pratama (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2024)
This research aims to determine the growth of turi plants on former gold mining land, by applying cow manure. This research was carried out at the BPDAS Palu Poso Permanent Nursery in the Tadulako University area. This research was carried out from April to November 2023. This research used a Completely Randomized Design (CRD) consisting of 4 treatments including P0= No Treatment, P1= 150 gr Manure P2= 200 gr Cow Manure P3= 250 gr Cow Manure. Each treatment was repeated 10 times so that there were 40 experimental units. The results of the analysis of variance showed that the growth of turi seedlings in ex-gold mining soil with the application of cow manure had a significant effect on the increase in height, diameter and number of leaves. The treatment that gave the best response was treatment P3= (250 gr of cow manure) with an average increase in height of 19.53 cm, an average increase in diameter of 0.72 mm, and an average increase in the number of leaves of 7.4 pieces.